Variabilidade da frequência cardíaca em trabalhadores da construção civil e de escritório - Souza, Letícia Ramos de (2016)
Background: The leisure physical activity has been linked to a number of benefits to health and the cardiovascular system. On the other hand, a high level of physical activity at work may be related to higher rates of cardiovascular disease and mortality in general. Thus, assessment of heart rate variability (HRV) in construction and office workers can provide information about the role of work in the cardiac autonomic modulation and hence the risk of cardiovascular disordes. Objective: To compare the autonomic modulation of heart rate in construction workers and office in supine and standing during the maneuver of respiratory sinus arrhythmia. Methods: The study inclued 34 male workers aged between 18 and 59 years. Exclusion criteria were: hypertension, diabetes mellitus, obesity, drug use and dyslipidemia. Participants underwent clinical evaluation, quality of life (SF-36), level of habitual physical activity (Baecke), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), stress (SRQ- 20), fatigue (Bipolar) and quality of sleep Pittsburgh (IQPS). The RR intervals were obtained by a heart rate monitor supine, standing and during the operation of respiratory sinus arrhythmia. Data analysis was done descriptively and through analysis of variance (ANOVA two way), considering the groups and assessment positions as independent variables and indices for HRV as dependent variables. Analyses were performed using SPSS software, with 5% significance level. Results: There were differences between the groups only for 2ULV index, and the group of construction workers showed greater parasympathetic modulation in relation to office workers group. There were differences between the positions for most of the indices, except for SDNN, BF, ES and 2LV. Conclusion: This study showed that the sedentary group has more sympathetic modulation in the supine position, which may be related to the lower complexity of HRV in this population.